Influence of reversible and non-reversible fatigue on the microstructure and mechanical property evolution of 7075-T6 aluminum alloy. (April 2021) - Indeck, Joseph; Demeneghi, Gabriel; Mayeur, Jason; Williams, Cyril; Hazeli, Kavan
Graphical abstract: Highlights: Microstructural evolution of 7075-T6 aluminum alloy after interrupted fatigue. Post-fatigue behavior is dependent on the type of fatigue and loading strain rate. Degradation of quasi-static strength correlated to fatigue-induced voids. Fatigue-induced voids occur in grains that inhibit slip transmission. Abstract: Evolution of microstructural features and defects caused by high cycle fatigue loading have the potential to affect post-fatigue global behavior in different ways depending on the material, fatigue loading parameters, and subsequent loading strain rate. This work focuses on the influence of reversible and non-reversible, macroscopic elastic fatigue on the microstructure and subsequent mechanical properties of 7075-T6 aluminum alloy. Subsurface material obtained from interrupted fatigue experiments is used for both microstructural characterization and post-fatigue mechanical property evolution. Crystal plasticity modeling, in conjunction with machine learning, is used to help determine mechanisms contributing to the mechanical property evolution. It was found that the subsequent mechanical behavior was dependent on both the fatigue stress ratio and subsequent loading strain rate. There was a 7% decrease in quasi-static strength after being fatigued with a stress ratio of zero. However, quasi-static strength remained unchanged after being fatigued at other stress ratios. In addition, dynamic tension experiments did not reveal any decreases in strength due to prior fatigue loading. Fatigue-induced voids potentially developed in grains where slip transmission across the grain boundary was less likely to occur. Iron-rich inclusion cracking took place throughout the bulk fatigued material and was mainly limited to larger sized inclusion particles, but there was no evidence it contributed to significant mechanical property changes. Results from this work show how different stress ratios and degrees of dislocation reversibility during high cycle fatigue loading influence the microstructure and post-fatigue global behavior of 7075-T6 aluminum alloy.